Is mediation violence? A critique of identity politics - Mazzone, Marco (Rivista Italiana di Filosofia del Linguaggio, 2024)
By «identity politics» (see Lilla 2017) I intend a political project closely based on the defense of the rights of individuals and minorities. Here, I analyze a problematic assumption that is sometimes made by the advocates of that project: the idea that, since difference is a value, no mediation is necessary, or even that behind every search for mediation lies a claim to universality that constitutes a form of violence. The dual purpose of this article is to challenge that critique of mediation through an analysis of the notion of universality, and to argue that the strategy proposed by identity politics is ultimately anti-political.